Hepatic and renal metallothionein concentrations in Commerson's dolphins (Cephalorhynchus commersonii) from Tierra del Fuego, South Atlantic Ocean - Cáceres Saez, Iris; Polizzi, Paula Sabrina; Romero, María Belén; Dellabianca, Natalia Andrea; Ribeiro, Sergio; Prosser Goodall, Rae Natalie; Cappozzo, Humberto Luis; Gerpe, Marcela Silvia (Marine Pollution Bulletin)
The Commerson's dolphin is the most common endemic odontocete of subantarctic waters of Tierra del Fuego, Argentina incidentally caught in fishing nets. The species is classified as "Data Deficient" by the IUCN. Metallothioneins (MTs) are considered as suitable biomarkers for health and environmental monitoring. The aims of the study were to assess MT concentrations in the liver and kidney of bycaught specimens. Moreover, correlations with Zn, Se, Cd, Ag and Hg, and the molar ratios of MT:metals were estimated to evaluate if there is an indication of their respective protective role against metal toxicity in tissues. Hepatic and renal MT concentrations were similar, ranging from 11.6 to 29.1 nmol·g-1 WW, and Kidney/Liver ratios ranging from 0.73 to 1.93 corresponded to normal ranges. Results suggest that MTs are related to physiological ranges for the species. This information constitutes the first MT report on Commerson's dolphins and possibly considered as baseline for species' conservation. Fil: Cáceres Saez, Iris. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Polizzi, Paula Sabrina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencia Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Romero, María Belén. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencia Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Dellabianca, Natalia Andrea. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. ...